Changing the diagnostic criteria for myocardial infarction in patients with a suspected heart attack affects the measurement of 30 day mortality but not long term survival. Issue 4 (1st October 2002) - Packham, C; Gray, D; Weston, C; Large, A; Silcocks, P; Hampton, J
Abstract : Objectives: To explore the effects of alternative methods of defining myocardial infarction on the numbers and survival patterns of patients identified as having sustained a confirmed myocardial infarct. Design: An inclusive historical cohort of patients admitted with a suspected heart attack. Patients were recoded from raw clinical data (collected at the index admission) to the epidemiological definitions of myocardial infarction used by the Nottingham heart attack register (NHAR), the World Health Organization (MONICA), and the UK heart attack study. Setting: Single health district. Patients: The NHAR identified all patients admitted in 1992 with suspected myocardial infarction. Outcome measures: Survival at 30 days and four year postdischarge. Results: 2739 patients were identified, of whom 90% survived to discharge. Recoding increased the numbers of patients defined as having confirmed myocardial infarction from 26% under the original NHAR classification to 69%, depending on the classification system used. In confirmed myocardial infarction, subsequent 30 day survival from admission varied from 77–86% depending on the classification system; four year survival after discharge was not affected. The distribution of important prognostic variables differed significantly between groups of patients with confirmed myocardial infarction defined by different systems. Patients with suspected but unconfirmed myocardial infarction under all classification systems had a worse postdischarge mortality. Conclusions: The classification system used had a substantial effect on the numbers of patients identified as having had a myocardial infarct, and on the 30 day survival. There were significant numbers of patients with more atypical presentations, not labelled as myocardial infarction, who did badly following discharge. More research is needed on these patients.